Discriminate me - if you can! The disappearance of the gender pay gap among public-contest selected employees - Carolina Castagnetti; Luisa Rosti; Marina Töpfer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2018)
This paper analyzes the effect of public-contest recruitment on earnings for men and women using Italian microdata over a time period of ten years. We find that the gender pay gap vanishes and even reverses among the young, when employees are selected through public contests. The results suggest that selection mechanisms such as public contests may offer a way for merit-based and gender-fair wage setting. However, since public contests and the public sector are highly correlated, we analyze the gender pay gap taking the interconnection between the public and private sector as well as the open contest issue into account. By decomposing our results by sector we find that public contests represent a necessary but not sufficient condition for merit-based and gender-fair recruitment. Similarly, the institutional environment of the public sector is a necessary but not sufficient condition for making public contests merit-based and gender-fair screening devices. These two factors taken together, cause the disappearance of the gender pay gap. – – Dieser Beitrag untersucht die Auswirkungen von Einstellungen durch öffetnlichen Wettbewerb (concorsi pubblici) auf den Verdienst von Männern und Frauen anhand italienischer Mikrodaten in einem Zeitraum von 10 Jahren. Er zeigt, dass das geschlechtsspezifische Lohndifferenzial im Mittel verschwindet, beziehungsweise umkehrt für unter 35-Jährige, wenn die Einstellung durchöffetnlichen Wettbewerb stattfindet. Dieses Ergebnis legt nahe, dass öffentliche Wettbewerbe gendergerechte und leistungsorientierte Einstellungsverfahren ermöglichen. Da das Prinzip des öffentlichen Wettbewerbs in Italien jedoch stark mit dem öffentlichen Sektor korreliert ist, betrachten wir das geschlechtsspezifische Lohndifferenzial (nach Einstellungsverfahren) separat für den öffentlichen und privaten Sektor. Dabei ergibt sich, dass öffentliche Wettbewerbe und der institutionelle Rahmen des öffentlichen Sektors notwendige aber keine hinreichenden Bedingungen für gendergerechte und leistungsorientierte Rekrutierung sind. Beide Faktoren zusammen führen zum Verschwinden des geschlechtsspezifischen Lohndifferenzials.
Keywords: J7; J13; J31; 330; Gender Pay Gap; Public-Contest Recruitment; Double Sample Selection